2022
DOI: 10.3390/rs14030519
|View full text |Cite
|
Sign up to set email alerts
|

Response of Precipitation in Tianshan to Global Climate Change Based on the Berkeley Earth and ERA5 Reanalysis Products

Abstract: Global climate change has readjusted a global-scale precipitation distribution in magnitude and timing. In mountainous areas, meteorological stations and observation data are very limited, making it difficult to accurately understand the response of precipitation to global climate change. Based on ECMWF Reanalysis v5 precipitation products, Berkeley Earth global temperature, and typical atmospheric circulation indexes, we integrated a gradient descent-nonlinear regression downscaling model, cross wavelet trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 106 publications
0
15
0
Order By: Relevance
“…The data are from 1950 to the present with a spatial resolution of 0.25° in latitude and longitude (Hersbach et al., 2020). The reanalysis procedure integrated instrumentation observations as well as available satellite data (Calì Quaglia et al., 2021; Daramola & Xu, 2022; Fan et al., 2022; Gleixner et al., 2020; Jiang et al., 2021). Monthly averaged surface air temperature and total precipitation from the data set are used in identifying climate types (Table 1) for our study period from 1960 to 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The data are from 1950 to the present with a spatial resolution of 0.25° in latitude and longitude (Hersbach et al., 2020). The reanalysis procedure integrated instrumentation observations as well as available satellite data (Calì Quaglia et al., 2021; Daramola & Xu, 2022; Fan et al., 2022; Gleixner et al., 2020; Jiang et al., 2021). Monthly averaged surface air temperature and total precipitation from the data set are used in identifying climate types (Table 1) for our study period from 1960 to 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Consistently, Fan et al. (2022) found that the North Pacific pattern (NP) and the Pacific interdecadal Oscillation (PDO) had an important impact on precipitation changes in Tianshan Mountains (the part within China) during 1979–2020, both of which indicate the influence of the Pacific Ocean on precipitation in the more eastern parts of the Tianshan Mountains. In addition, the anomalous anticyclone located in western Siberia conveys moisture from Siberia to the Eastern Tianshan, accounting for the increased moisture contribution from Siberia of 9.9% (average: 5.2%) during extreme precipitation in Eastern Tianshan.…”
Section: Discussionmentioning
confidence: 79%
“…About 97.52% of the glaciers in the Tianshan Mountains show retreating trends from the 1960s to 2010s (Chen et al., 2016) which is in accordance with the increasing temperature trend over decades (Hu, 2004; Jiang et al., 2013). On the contrary, precipitation in the Tianshan has shown an overall upward trend (Chen et al., 2016; Fan et al., 2022; Guan et al., 2021a; Sorg et al., 2012; S. Wang et al., 2013; Yang & He, 2003; Yuan et al., 2004; Zhang et al., 2009), although some studies suggest that a significant decrease in precipitation has been observed in Western Tianshan (Guan et al., 2021a; Hu et al., 2017). In addition to interannual variability, there is also multi‐scale decadal variability in Tianshan precipitation (Guan et al., 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the significant difference in annual variation of precipitation in the Tianshan Mountains [12,13], according to the application of the index station method [84,85], and with reference to the annual distribution of multi-year average precipitation and consecutive maximum precipitation months of representative stations in the Tianshan Mountains [18], the wet season is determined from April to August, and the dry season is determined from September to March of the next year. The index station method is by selecting observation stations that cover the whole study period and have almost no lack of measurement; the wet season is divided according to the monthly average precipitation of each station during the study period [86,87].…”
Section: Annual Scale Accuracy Assessmentmentioning
confidence: 99%
“…The glaciers and snow in the Tianshan Mountains are important water resources in Central Asia and are affected by precipitation changes [5,[9][10][11]. Global warming accelerates the hydrological cycle [12,13]. By changing the redistribution of water energy in the atmosphere, precipitation in the Tianshan Mountains not only has an important impact on climate change in the glacier region but also affects the natural ecological environment and social and economic activities [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%